1992
DOI: 10.1210/endo.130.6.1597143
|View full text |Cite
|
Sign up to set email alerts
|

Roles of interleukin-1 alpha and -1 beta in endotoxin-induced suppression of plasma gonadotropin levels in rats.

Abstract: Using specific antagonists to rat interleukin (IL)-1 alpha and IL-1 beta, the roles of these IL-1s in endotoxin-induced suppression of plasma gonadotropin levels in freely-moving rats were studied. In orchiectomized rats, recombinant rat IL-1 alpha and IL-1 beta administered into the lateral ventricles almost equipotently suppressed plasma LH levels. Twenty five micrograms of bacterial endotoxin or lipopolysaccharide (LPS) administered similarly showed a comparable effect as that of 1 microgram IL-1 alpha or I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…Our conclusion in the non-human primate is different from data in the rodent in which IL-1ra was shown to interfere with LPS-induced ACTH and corticosterone release [16,24]. However, also in the rodent [25], IL-1ra appears to be capable only of attenuating the LH inhibitory effects of intracerebroventricular LPS during the first 60 min but not thereafter, suggesting that, if any, the role of IL-1 in mediating these effects of LPS on LH secretion is limited. No early effects of IL-1ra were observed in the monkey, perhaps reflecting varying experimental conditions or a species-specific difference.…”
Section: Discussioncontrasting
confidence: 98%
“…Our conclusion in the non-human primate is different from data in the rodent in which IL-1ra was shown to interfere with LPS-induced ACTH and corticosterone release [16,24]. However, also in the rodent [25], IL-1ra appears to be capable only of attenuating the LH inhibitory effects of intracerebroventricular LPS during the first 60 min but not thereafter, suggesting that, if any, the role of IL-1 in mediating these effects of LPS on LH secretion is limited. No early effects of IL-1ra were observed in the monkey, perhaps reflecting varying experimental conditions or a species-specific difference.…”
Section: Discussioncontrasting
confidence: 98%
“…Central injections of LPS have been shown to induce brain expression of pro-inflammatory cytokines and to depress social behavior in rats, increase the duration of immobility, and induce body weight loss (Bluthé et al, 1999). Moreover, endotoxin given experimentally to the brain region affected the functioning of the central nervous system and led to strong suppression of the peripheral LH level (Ebisui et al, 1992). A study performed on chimeric mice showed that TLR4 is crucial for sustained inflammation in the brain after peripheral administration of LPS and that its function in CNS-resident cells is independent of systemic cytokine effects (Chakravarty and Herkenham, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this paradoxical effect on LH secretion is unclear, this might be caused by a direct action of LPS on the pituitary as suggested from in vitro experiment [4]. In laboratory rodents, recent studies on the neural mechanism underlying the immunological suppression of basal LH secretion and the preovulatory LH surge release [2,6,9,10,14,[19][20][21][22]27] have led to a concept outlined as follows. First, peripheral immune cells are activated following the immunological challenge like the LPS administration, and a number of cytokines are released from these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been made to clarify the mechanism underlying this suppression, and it has been revealed that an immunological activation of host animal results in a reduction of luteinizing hormone (LH) secretion from the pituitary gland and/or direct suppression of gonadal function in several species [4,8,14,18,[23][24][25]27]. In rodents, for instance, the administration of lipopolysaccharide (LPS), an endotoxin of gram negative bacteria, or cytokines released from immune cells during the acute phase of infection suppresses secretion of gonadotropin-releasing hormone (GnRH) and LH [2,6,9,10,19]. This inhibitory effect on the hypothalamic-pituitary gonadal (HPG) axis is thought to be mediated by the mechanism which is independent from that for the activation of hypothalamic-pituitary adrenal (HPA) axis [20,23].…”
Section: Methodsmentioning
confidence: 99%